2022
DOI: 10.1021/acsami.2c17477
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Sub-Gap States to Broadband Infrared Response in Organic Bulk Heterojunctions

Abstract: This work studied a series of infrared detectors comprised of organic bulk heterojunctions to explain the origin of their broadband spectral response from the visible to the infrared spanning 1 to 8 μm and the transition from photonic to bolometric operation. Through comparisons of the detector current and the sub-bandgap density of states, the mid-and long-wave infrared response was attributed to charge trap-and-release processes that impact thermal charge generation and the activation energy of charge mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…3,14,30 It is reported that organic semiconductors with abundant midgap states tend to respond to thermal signals with wavelengths located in the midwave and long-wave infrared. 31 These results are encouraging for the design of organic upconversion imagers for different wavebands. To facilitate human eye vision, green organic LEDs are most frequently employed in upconversion devices since human eyes are naturally sensitive to green photons.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 79%
See 1 more Smart Citation
“…3,14,30 It is reported that organic semiconductors with abundant midgap states tend to respond to thermal signals with wavelengths located in the midwave and long-wave infrared. 31 These results are encouraging for the design of organic upconversion imagers for different wavebands. To facilitate human eye vision, green organic LEDs are most frequently employed in upconversion devices since human eyes are naturally sensitive to green photons.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 79%
“…Device designs such as incorporating etalon structures, photonic structures, and so on, are also effective ways to adjust the response spectrum of organic detectors. The light absorption of organic semiconductors can cover a very broad spectrum ranging from ultraviolet to SWIR wavelengths. Benefiting from the photovoltaic field, the organic materials sensitive to visible and near-infrared (NIR) light are very mature. ,,, Organic materials with sensitivity to SWIR wavelengths are still under development. ,, It is reported that organic semiconductors with abundant midgap states tend to respond to thermal signals with wavelengths located in the midwave and long-wave infrared . These results are encouraging for the design of organic upconversion imagers for different wavebands.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 99%
“…The response for λ < 1.7 μm is photonic, and the response for the 38 μm is bolometric. Parts (k) and (l) are reproduced with permission from ref .…”
Section: Infrared Detector Designsmentioning
confidence: 99%
“…Recently, Li et al demonstrated a promising thermal response in organic BHJ detectors . The BHJ detectors combined photonic and bolometric mechanisms to achieve broadband detection spanning the visible to longwave infrared (0.4–8 μm), with photonic charge generation for visible to shortwave infrared light (0.4–1.5 μm) and bolometric effects for the midwave infrared to longwave infrared (3–8 μm).…”
Section: Infrared Detector Designsmentioning
confidence: 99%
See 1 more Smart Citation